2021
DOI: 10.3390/cancers13174424
|View full text |Cite
|
Sign up to set email alerts
|

Urological Melanoma: A Comprehensive Review of a Rare Subclass of Mucosal Melanoma with Emphasis on Differential Diagnosis and Therapeutic Approaches

Abstract: Melanoma is reported as the 19th most common cancer worldwide, with estimated age-standardized incidence rates of 2.8–3.1 per 100,000. Although the origin is most frequently cutaneous, mucosal melanoma has been described several times in literature, and despite its rarity (only 1% of all melanomas), increasing attention is being paid to this disease form. Within this subgroup, melanomas of the uropoetic apparatus are a rarity among rarities. Indeed, less than 50 cases of primary melanoma originating from the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 99 publications
0
11
0
Order By: Relevance
“…KIT is frequently mutated in VM, such as other urogenital melanomas, regardless of the employed technology [ 25 , 31 , 32 , 34 , 35 , 36 , 37 , 38 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Exon 11 L576P KIT mutation has been frequently detected [ 31 , 32 , 35 , 36 , 40 , 41 , 43 , 46 ], suggesting Imatinib or Sunitinib as a possible use [ 31 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…KIT is frequently mutated in VM, such as other urogenital melanomas, regardless of the employed technology [ 25 , 31 , 32 , 34 , 35 , 36 , 37 , 38 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Exon 11 L576P KIT mutation has been frequently detected [ 31 , 32 , 35 , 36 , 40 , 41 , 43 , 46 ], suggesting Imatinib or Sunitinib as a possible use [ 31 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The rapid growth of a myometrial lesion may be suspected. However, the meaning of "rapid growth" is not well defined [13,14]. Additionally, studies have shown that even benign lesions can increase their size by 18% to 120% per year [15].…”
Section: Discussionmentioning
confidence: 99%
“…Platinum-based NACT followed by radical hysterectomy has been suggested as an alternative approach to radiotherapy or CCRT in LACC, particularly for those with squamous cell histology, with objective response rates varying from 69.4-90.2%, pathological optimal response rates from 21.3-48.3%, 5-year disease-free survival (DFS) rates ranging from 55.4-71% and 5-year OS rates ranging from 58.9-81%, respectively (47)(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%